The 'tears' score: A tool for grading and monitoring epiphora. Issue 4 (July 2022) - Schulz, Christopher B.; Malhotra, Raman
Purpose: To test the reliability, validity and utility of the TEARS score, a scale of clinical and patient-reported severity in patients with epiphora, comprising 4 subscales: Times wiping (T), clinical Effects (E), Activity limitation (A), and symptoms of Reflex epiphora (R). Methods: The TEARS score was completed by 136 patients with epiphora (78 treated surgically, and 51 non-surgically). Inter-rater reliability was evaluated using Cohen's Kappa and Bland-Altman analysis. 129 (95%) participants were followed up 2–6 months after baseline (non-surgical patients) or 3–6 months post-operatively (surgical patients). For each TEARS subscale, differences in scores were compared. Convergent validity was evaluated by testing correlation between TEARS and both The Lacrimal Symptom Questionnaire (Lac-Q) and The Watery Eye Quality of Life Score (WEQOL). Results: Inter-rater reliability (Cohen's K) ranged from 0.5 for 'A' and 'R' to 0.8 for 'T' and 'E' subscales. Scores were lower post-operatively in surgical patients (p < 0.001). 'R' scores (reflex tearing) were higher in non-surgical cases compared with surgical (p = 0.02) but no difference was observed in other subscales at baseline. TEARS subscale scores were positively correlated with both WEQOL (r = 0.51 to 0.73) and Lac-Q score (r = 0.55 to 0.63). Conclusion: The TEARS score is quickly and easily implemented in a busy clinical setting. It provides an overview of both subjective and objective clinical severity in patients with epiphora, with appropriate reliability, post-operative responsiveness and convergent validity for this purpose and in this setting. It is a valuable template to be used alongside individualised symptomology.